Mosquito squadron - Rachmil, Lewis J., 1908-1984.; Sagal, Boris, 1923-1981.; Sanford, Donald S.; Perry, Joyce; McCallum, David, 1933-; Neve, Suzanne, 1939-; Gray, Charles D., 1928-2000.; Thorpe-Bates, Peggy; Henson, Nicky; Marshall, Bryan, 1938-; Oakmont Productions; MGM Home Entertainment Inc. (Santa Monica, Calif. : MGM Home Entertainment, 2003)
Two fighter pilots become close friends while fighting for the R.A.F in World War II. When one of the pilots dies, the survivor develops a relationship with his dead friend's wife. Director Boris Sagal's movie features incredible footage of the Mosquito bomber planes used by the R.A.F. And the final sequence has been cited as an influence on George Lucas's Death Star sequences in Star Wars.
Originally released as a motion picture in 1970.
Special features: original theatrical trailer.
Music, Frank Cordell.
David McCallum, Suzanne Neve, Charles Gray, Peggy Thorpe- Bates, Nicky Henson, Bryan Marshall.
MPAA rating: G.
DVD, widescreen presentation (aspect ratio, 1.66:1); Dolby Digital mono.
Keywords: Great Britain. -- Royal Air Force -- Drama; World War, 1939-1945 -- Aerial operations, British -- Drama; Fighter pilots -- Drama; Mosquito (Military aircraft) -- Drama; Man-woman relationships -- Drama; Video recordings for the hearing impaired; Feature films; War films; Action and adventure films